Intelligent dynamic directional assembly-disassembly soft tissue repair material and preparation and application thereof

By using nucleophilic addition reactions of biopolymers with amine compounds and negative pressure adsorption technology, stable chemical covalent bonds are formed. Combined with pH and long-wave stimulation, the directional assembly-disassembly of soft tissue repair materials is achieved, solving the safety and control issues of existing materials and providing adaptability to multiple occasions and long-lasting repair effects.

CN121445951APending Publication Date: 2026-02-03UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511571739.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Existing soft tissue injury repair materials have problems such as poor safety, easy to cause tissue fibrosis, infection and inflammation, and the structure and degradation of ordinary materials are uncontrollable.

Method used

Biopolymer materials and amine compounds are reacted via nucleophilic addition to form oriented, highly oxidized structures. Stable chemical covalent bonds are formed by negative pressure adsorption and multi-level semi-permeable membrane reactions. The material is then oriented to assemble and disassemble by pH and long-wave stimulation.

Benefits of technology

We have developed a variety of soft tissue repair materials with diverse forms, adaptability to various occasions, good biocompatibility, strong injectability, and suitable mechanical properties. These materials are used for various soft tissue repairs, offering high safety, low cost, easy operation, and long-lasting repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121445951A_ABST
    Figure CN121445951A_ABST
Patent Text Reader

Abstract

The invention discloses an intelligent dynamic directional assembly-disassembly soft tissue repair material as well as preparation and application thereof, and belongs to the technical field of intelligent soft tissue repair materials. By selecting proper target materials and using different modification methods and special preparation modes for different forms of target materials, the target materials have oriented high-oxidation-state structures or highly-uniform high-oxidation-state structures, amine compounds are selectively subjected to long-wave response function modification, and through pH change and long-wave stimulation, the long-wave response function of the amine compounds is improved. And regionalized directional dynamic assembly-disassembly of the composite material is realized. The repair material has the advantages of multiple forms, multi-occasion adaptability, simplicity and convenience in operation, good biocompatibility, proper viscosity and injectability, proper mechanical property and degradability, excellent tissue repair performance and the like, and is used for repairing various soft tissues; the method includes repairing endometrium, vagina, abdominal cavity endometrium, cartilage, skin superficial trauma, digestive tract, stomach wall, urethra and the like and eliminating skin scars.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an intelligent dynamic directional assembly-disassembly soft tissue repair material, its preparation and application, and belongs to the field of intelligent materials technology for soft tissue repair. Background Technology

[0002] Soft tissue injury refers to acute trauma caused by certain diseases or chronic strain accumulated from long-term overuse by various external factors or the body itself. Clinically, soft tissue injury can be divided into chronic soft tissue injury (CHTI) and acute soft tissue injury (ACTI). Generally speaking, CHTI is a condition with a slow onset, where various tissues become damaged due to overuse. CHTI is a common and frequently occurring disease that endangers human health. In 2003, according to statistics from Harvard University School of Health Sciences, the losses caused by back and leg pain in the United States alone were approximately $7 billion, and in the United Kingdom, more than 10 million people were absent from work each year due to back pain. ACTI, on the other hand, refers to soft tissue injury caused by external stimulation. The injured area develops aseptic inflammation, and over time, the soft tissue develops adhesions of varying degrees and excessive proliferation of fibrotic tissue, leading to scar formation and soft tissue fibrosis. When ACTI is not treated in time, it will gradually develop into CHTI. Soft tissue injury occurs with extremely high frequency in today's society. Currently, autologous tissue transplantation, stem cell therapy, drug therapy, and surgery are the main treatments for soft tissue injuries. While the research by AM Harmon and LJ Brown et al., "A Method for the Preparation of Soft Tissue Repair and Regeneration Using Stem Cell Products," showed significant effectiveness, it also suffered from a series of problems, including poor safety, tissue fibrosis, infection, and inflammation. Therefore, developing natural biomaterials with repairing effects is crucial for soft tissue repair. Ordinary tissue repair materials suffer from drawbacks such as uncontrollable structure, degradation, and release, making smart materials a promising area for soft tissue repair.

[0003] Among natural biomaterials, polysaccharides have a large molecular weight and unique structure, typically existing as a main chain with side chain groups. This determines their diverse rheological properties and allows for reasonable modification as needed. They also possess abundant hydroxyl groups and spatial folding, exhibiting good hydrophilicity and emulsifying ability, readily forming gels in water with high viscosity. Furthermore, they are easily modified to possess smart responsiveness. Polysaccharides have various functions, including antioxidant activity, ulcer prevention, inflammation relief, and immune system regulation. Natural polysaccharides such as chitosan, alginate, and gelatin are widely available, low in cost, low in toxicity, possess excellent bioactivity, and good biocompatibility, making them commonly used as various soft tissue engineering repair materials. Summary of the Invention

[0004] This invention addresses the problems of poor safety and easy occurrence of tissue fibrosis, infection and inflammation in existing soft tissue repair materials. It proposes an intelligent dynamic directional assembly-disassembly soft tissue repair material, its preparation method and its application.

[0005] The present invention is based on the following approach: selecting biopolymer materials as target materials, choosing different modification methods according to the different morphologies of the materials, and using reagents with strong electron-gaining capabilities to upgrade the oxidation state of the target materials, including but not limited to carbon-hydrogen bond breaking and recombination, and substitution by hybrid atoms. Different methods are used to enable the target materials to form oriented or highly homogeneous high-oxidation-state structures.

[0006] Then, amine compounds (because their structures contain atoms with lone pairs of electrons, including but not limited to nitrogen atoms, which spontaneously attack the positively charged carbon atoms on the carbonyl groups of the target material) or other substances with lone pairs of electrons are used to complete nucleophilic addition reactions, forming intermediate α-hydroxy compounds, which are then further dehydrated to form covalent bonds. Amine compound molecular chains can provide better, gentler, and longer-lasting targeted treatment for soft tissue injuries through directed assembly-disassembly.

[0007] If the target material is solid, it can form an oriented high-oxidation-state structure through multiple directional negative pressure adsorption processes. This structure then reacts with amine compounds under negative pressure adsorption to assemble into an oriented composite material with gradient chemical covalent bonds. During acidic-alkaline transformations, the concentration gradient caused by the oriented chemical bonds induces the directional assembly and disassembly of the amine compound molecular chains within the composite material.

[0008] The orientation degree of the material can be controlled by adjusting the pressure of negative pressure adsorption, the concentration of amine compounds, and the number of negative pressure adsorption cycles. If the substance contains atoms with lone pairs of electrons and is a polymer, it can also help the molecular chains entangle between the molecular chains of the target material, forming a more stable multi-layered network.

[0009] If the target material is liquid, it can be reacted through a hierarchical semi-permeable membrane with small and large pores. Through slow, uniform diffusion and in-situ reaction, a highly uniform high-oxidation-state structure is formed. The uniformly distributed carbonyl groups guide atoms with lone electrons to attack positively charged carbon atoms, resulting in relatively uniform chemical covalent bonds. Similarly, this hierarchical semi-permeable membrane can also provide a reaction site, allowing amines and polysaccharides to undergo Michael addition reactions, which are then endowed with long-wavelength (300-400 nm) UV response characteristics, and the distribution of relevant functional groups is also highly uniform. After the high-oxidation-state target material and the long-wavelength responsive amines are dissolved and mixed uniformly under weakly acidic conditions, the environment is changed to a weakly alkaline environment, assembling to form uniform chemical bonds. The distribution of relevant functional groups is also highly uniform. The amines and the high-oxidation-state target material are evenly distributed through free diffusion and entanglement, and the molecular chain structure is more compact, which is conducive to the next reaction. After changing to a weakly alkaline environment, the two assemble to form highly uniform chemical bonds. At this point, the material viscosity increases, but it remains liquid and is injectable. The liquid material undergoes secondary cross-linking under ultraviolet long-wave (300-400nm) stimulation, transforming from a liquid to a solid state. This dual cross-linking makes the material structure more stable and its mechanical strength higher. When the environment becomes acidic, the primary chemical bonds break, the material phase remains unchanged, but its structure and mechanical properties change. Under infrared and other long-wave directional stimulation, the molecular chains undergo violent vibrations, and amine compounds undergo directional assembly and disassembly.

[0010] The specific plan is as follows: This invention provides an intelligent dynamic directional assembly-disassembly soft tissue repair material. A smart dynamic directional assembly-disassembly soft tissue repair material, characterized in that: the soft tissue repair material is made from biopolymer materials and amine compounds through a nucleophilic addition reaction; The nucleophilic addition reaction is as follows: the atom with lone pair electrons in the amine compound attacks the carbon atom with positive charge on the carbonyl group in the biopolymer to form an α-hydroxy compound, which is then dehydrated to form a covalent bond, thus obtaining the amine compound molecular chain; The aforementioned biopolymer materials are treated with reagents that have strong electron-gaining ability to upgrade their oxidation state; The aforementioned biopolymer materials are either solid biopolymer materials or liquid biopolymer materials; If the biopolymer material is a liquid biopolymer material, the amine compound that undergoes affinity addition with it should first be modified by reacting with a Michael addition reagent; The aforementioned amine compound molecular chains are used to repair soft tissue damage through directed assembly-disassembly.

[0011] Specifically, The solid biopolymer material is specifically one or a combination of two or more of the following: dextran, lignin, cellulose, bacterial cellulose, cellulose nanomaterials, gelatin, polyurethane, or PLA. The liquid biopolymer material specifically comprises one or more of the following: chitosan, chitosan derivatives, alginate, modified alginate, polypeptides, proteins, or collagen.

[0012] The aforementioned biopolymer materials are required to have good biocompatibility, no biotoxicity, and a certain morphology and strength after treatment, and to have electron-losing groups. Natural biomaterials and artificially synthesized materials with these properties can be used as precursors for the preparation of the soft tissue repair materials described in this invention.

[0013] The amine compounds are selected from polysaccharides, proteins, collagen, polypeptides, growth factors, or nucleic acids.

[0014] The aforementioned amine compounds are required to contain atoms with lone pairs of electrons, including but not limited to the N atom on the amino group, and to be non-biotoxic. Substances that promote soft tissue repair can be used as precursors for the preparation of the soft tissue repair material described in this invention.

[0015] This invention also provides a method for preparing intelligent dynamic directional assembly-disassembly soft tissue repair materials.

[0016] A method for preparing an intelligent dynamic directional assembly-disassembly soft tissue repair material, characterized by comprising the following steps: Step 1: The solid biopolymer material is subjected to a first negative pressure adsorption using a neutral-weakly alkaline buffer solution. The preferred reaction conditions for negative pressure adsorption are a pressure of 0.2 MPa-2 MPa and a time of 30 s-600 s.

[0017] The neutral-weakly alkaline buffer solution is selected from tris(hydroxymethyl)aminomethane (Tris) solution, triethanolamine solution, glycine-sodium hydroxide solution, or sodium carbonate-sodium hydroxide solution.

[0018] This step provides a favorable reaction microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the conditions for subsequent reactions would be insufficient, electron transfer would be difficult, and the reaction would be unstable and unsustainable.

[0019] Step 2: A second negative pressure adsorption is performed using a strong electron-gaining reagent solution (the solvent being a commonly used buffer solution compatible with the strong electron-gaining reagent). The strong electron-gaining reagent is ferric chloride, sodium periodate, potassium permanganate, and sodium hypochlorite, etc., and the concentration of the strong electron-gaining reagent solution is 1 wt%-10 wt%. Due to pressure, most of the solute is concentrated in the lower layer, resulting in a "low-high" solution concentration gradient inside the solid biopolymer material. Ions move from top to bottom, thus simultaneously creating a "low-high" stepwise reaction degree.

[0020] Step 3: Perform negative pressure adsorption 2-4 times using a neutral-weakly alkaline buffer solution; This step promotes the forward reaction between the solid biopolymer material and the reagent with strong electron-accepting ability, making the chemical bonds formed more stable and fostering the formation of a "low-high" chemical bond gradient within the target material, while simultaneously restoring a favorable reaction microenvironment. When the negative pressure adsorption occurs less than twice, the chemical bonds formed are unstable; when the number of adsorptions exceeds five times, it can easily cause deformation of the target material and significant changes in its structure.

[0021] Step 4: Perform negative pressure adsorption 2-4 times using an amine compound solution; during this negative pressure adsorption, the solid polymer material undergoes a nucleophilic addition reaction with the amine compound.

[0022] This step also creates a "low-high" solution concentration gradient within the solid biopolymer material, causing ions to move from top to bottom, thus simultaneously forming a "low-high" stepwise reaction and creating "few-many" chemical bonds. Repeating this process 2-4 times is necessary. When the negative pressure adsorption is repeated less than 3 times, the chemical bonds formed are unstable, and the amount assembled is small. When the number of repetitions is greater than 4 times, the excessive amount of assembly leads to the easy detachment of the solid biopolymer molecular chains, causing deformation of the target material and significant changes in its structure.

[0023] Step 5: Perform negative pressure adsorption 2-5 times using a neutral-weakly alkaline buffer solution to obtain intelligent dynamic directional assembly-disassembly soft tissue repair material.

[0024] This step stabilizes the chemical bonds formed in the reaction and restores a favorable reaction microenvironment. When the negative pressure adsorption occurs less than twice, the chemical bonds formed in the reaction are unstable; when the number of adsorptions exceeds five, it can easily cause deformation of the target material and significant changes in the material structure.

[0025] The weakly alkaline buffer solution mentioned in steps 1, 3 and 5 above is preferably a tris(hydroxymethyl)aminomethane (Tris), triethanolamine, glycine-sodium hydroxide or sodium carbonate-sodium hydroxide solution; its concentration is 5 wt%-20 wt%.

[0026] In steps 1-5 above, the negative pressure adsorption pressure is 0.2MPa-2MPa, and the time is 30s-600s.

[0027] A method for preparing an intelligent dynamic directional assembly-disassembly soft tissue repair material, characterized by comprising the following steps: Step 1: Dissolve the amine compound in buffer solution to prepare a 3-10 wt% solution. Place the solution in a semi-permeable membrane at 1000 kPa-2000 kPa and seal it to obtain a primary reaction environment. Step 2: Place the primary reaction environment obtained in Step 1 into a Michael addition reagent solution for reaction. The Michael addition reagent is methacrylic anhydride or methacrylamide, with a solution concentration of 15%-20%, a reaction temperature of 20℃-40℃, and a reaction time of 6-12h. In this step, the electron-gaining reagent molecules slowly enter the primary reaction environment through the semi-permeable membrane and react with amine compound molecules. This allows for controlled reaction rates, resulting in a more uniform and complete reaction, preventing uneven reaction and clumping. Meanwhile, harmful molecules in the electron-gaining reagent solution are kept outside the semi-permeable membrane.

[0028] Step 3: Place the liquid in the primary reaction environment obtained in Step 2 into a semi-permeable membrane of 3000 kPa-7000 kPa and seal it to obtain the secondary reaction environment. Step 4: Place the secondary reaction environment obtained in Step 3 into a Michael addition reagent solution for reaction. The Michael addition reagent is methacrylic anhydride or methacrylamide, with a solution concentration of 5%-15%, a reaction temperature of 20℃-40℃, and a reaction time of 6-12h. After the first-order reaction, most of the groups are reacted, which makes the reaction more complete and ensures that the reaction of all molecular chains occurs simultaneously.

[0029] Step 5: Place the liquid in the secondary reaction environment described in Step 4 into a semi-permeable membrane of 10000kpa-15000kPa and seal it to obtain the tertiary reaction environment. Step 6: Place the tertiary reaction environment obtained in Step 5 into PBS solution to react and obtain modified amine compounds; replace the PBS solution every 6-12 hours, the reaction temperature is 30℃-40℃, the total reaction time is 48-96 hours, and the total number of replacements is greater than 3. In a tertiary reaction environment, all reactions gradually cease, and residual small molecules diffuse out of the semipermeable membrane. This ensures the homogeneity and biocompatibility of the modified amine compounds. Replacing the semipermeable membrane less than three times will result in heterogeneity of the amine compounds and the presence of residual small molecules. If the membrane pore size is too large, the reaction will be too rapid, leading to heterogeneity of the amine compounds and easy loss of amine compounds. If the membrane pore size is too small, molecules will have difficulty passing through, resulting in an overly slow reaction or even no reaction at all, and excessive molecular residue.

[0030] Step 7: Dissolve the liquid biopolymer material in a neutral-weakly alkaline buffer solution to prepare a 5%-10% solution, and place the solution in a 500kPa-1000kPa semipermeable membrane as the primary reaction environment. Step 8: Place the primary reaction environment obtained in Step 7 into a strong electron-gaining reagent solution (the solvent is a commonly used buffer solution adapted to the strong electron-gaining reagent) for reaction. The concentration of the strong electron-gaining reagent solution is 5%-10%, the reaction temperature is 20℃-30℃, and the reaction time is 1-2h. Molecules with strong electron-gaining ability slowly enter the primary reaction environment through a semi-permeable membrane and react with the molecular chains of liquid biopolymers. This allows the reaction rate to be controlled, the reaction to be more uniform and complete, and avoids the phenomenon of inconsistent oxidation state upgrades.

[0031] Step 9: Seal the liquid in the primary reaction environment described in Step 8 into a semi-permeable membrane with a pressure of 1000 kPa-5000 kPa to obtain a secondary reaction environment. Step 10: Place the secondary reaction environment obtained in Step 9 in a strong electron-gaining reagent solution (the solvent is a commonly used buffer solution adapted to the strong electron-gaining reagent) for reaction. The concentration of the strong electron-gaining reagent solution is 1%-5%, the reaction temperature is 20℃-30℃, and the reaction time is 1-2h. After the first-order reaction, most of the groups are reacted, which makes the reaction more complete, ensures that the reaction of all molecular chains occurs simultaneously, stabilizes the reaction rate, and ensures the uniformity of the products.

[0032] Step 11: Place the liquid in the secondary reaction environment described in Step 10 into a semi-permeable membrane of 5000kpa-10000kPa and seal it to obtain the tertiary reaction environment. Step 12: Place the tertiary reaction environment obtained in Step 11 into PBS solution to react and obtain liquid biopolymer material with upgraded oxidation state; replace the PBS solution every 6-12 hours, the reaction temperature is 30℃-40℃, the total reaction time is 48-96 hours, and the total number of replacements is greater than 3. In the tertiary reaction environment, all reactions gradually cease, and residual small molecules diffuse out of the semipermeable membrane. This ensures the homogeneity and biocompatibility of the target material after oxidation state upgrade. Replacing the semipermeable membrane less than three times will result in uneven loading and residual small molecules. If the membrane pore size is too large, the reaction will be too rapid, causing uneven loading and easy loss of large molecules. If the membrane pore size is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0033] Step 13: Prepare a 5%-20% solution of the modified amine compound obtained in step 6 and the upgraded oxidized liquid biopolymer material obtained in step 13 with acidic buffer solution, mix them evenly, and then add an alkaline buffer solution to carry out a nucleophilic addition reaction. After reacting for 1-5 hours, a smart dynamic directional assembly-disassembly soft tissue repair material is obtained.

[0034] The preferred acidic buffer is 50 mM Glycine-HCl, 50 mM acetate buffer, or 50 mM citrate buffer; the preferred alkaline buffer is 50 mM carbonate buffer.

[0035] The present invention also provides an intelligent dynamic directional assembly-disassembly soft tissue repair material prepared by the method, and the application of the material.

[0036] This intelligent, dynamically oriented assembly-disassembly soft tissue repair material is an implantable repair material with multiple morphologies and applications, ease of use, good biocompatibility, suitable viscosity and injectability, appropriate mechanical properties and biodegradability, and excellent tissue repair performance. It can be used for various soft tissue repairs, including endometrial repair, vaginal repair, peritoneal repair, cartilage repair, superficial skin wound repair, scar removal, digestive tract repair, stomach wall repair, and urethral repair.

[0037] An application of an intelligent dynamic directional assembly-disassembly soft tissue repair material, characterized by: The aforementioned soft tissue repair material repairs soft tissue damage by implanting it into or covering the damaged area. This soft tissue repair material is prepared based on solid biopolymers.

[0038] The repair material exhibits strong chemical bonds and high mechanical properties when placed in an alkaline environment, resulting in structural stability. However, when placed in a weakly acidic environment, the chemical reaction reverses, causing the chemical bonds to break and amine compounds to dissociate and release. This leads to a decrease in the material's mechanical properties and may even cause it to transition from a solid to a viscous flow state. When the pH of the surrounding environment increases again, the chemical bonds gradually stop breaking, and the remaining amine molecules re-bond to the material surface, achieving an assembly-disassembly process.

[0039] The environment at the damaged site is generally acidic, prompting the reverse chemical reaction and the breaking of chemical bonds. Due to the presence of oriented chemical bonds, amine compounds are released in a directional dissociation from top to bottom, leading to a decrease in the material's mechanical properties and even a transformation from a solid to a viscous flow state. When the repair is complete, the pH value at the damaged site rises, and the amine compounds stop disassembling and reassemble. The amine compounds near the material reassemble back into the target material, thus offering the potential for long-term and effective repair of soft tissue.

[0040] An application of an intelligent dynamic directional assembly-disassembly soft tissue repair material, characterized by: The aforementioned soft tissue repair material is injected into the damaged soft tissue site to repair soft tissue damage. This soft tissue repair material is prepared based on liquid biopolymers.

[0041] The repair material has high viscosity and can be injected into containers of any shape and space. It utilizes long-wavelength initiation to initiate self-polymerization, causing secondary cross-linking reactions in the amine compounds, transforming the material into a solid state. When the environment becomes acidic, primary chemical bonds break; the material phase remains unchanged, but its structure and mechanical properties alter. Under long-wavelength directional stimulation such as infrared light, the molecular chains undergo violent vibrations, and the amine compounds undergo directional assembly and disassembly.

[0042] This repair material is directly injected into the damaged soft tissue via injection, a simple procedure that allows the composite material to permeate the damaged area, increasing the contact area and probability between active groups and active factors and the tissue. It can also be used when filling is required at the repair site. Based on its properties, in practical applications, the repair material remains stable in a liquid state before injection. After injection and molding, the environment at the damaged site is generally weakly acidic. At this point, primary chemical bonds break, the material phase remains unchanged, but its structure and mechanical properties change. Amine compounds directionally enter the damaged tissue to exert their repair function. By changing the pH value and using infrared wavelengths to initiate self-polymerization, the molecular chains undergo violent vibrations, causing secondary cross-linking reactions in the amine compounds. This directional assembly-disassembly alters the distance between molecular chains, significantly changing the viscosity, and transforming the material into a solid or semi-solid state. This process allows the material to remain at the damaged site for a longer period.

[0043] An application of an intelligent dynamic directional assembly-disassembly soft tissue repair material, characterized by: The aforementioned soft tissue repair material is applied to the repair of the epidermis.

[0044] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The intelligent dynamic directional assembly-disassembly soft tissue repair material prepared by this invention is constructed through two types of intelligent dynamic directional assembly-disassembly soft tissue repair materials: oxidation state orientation upgrading, oxidation state uniform upgrading, construction of materials with oriented chemical bonds with amine compounds, advanced uniform Michael addition reaction of polysaccharides, and pH and long-wavelength induced material assembly-disassembly. This material is an implantable repair material with multi-morphological and multi-application adaptability, ease of operation, good biocompatibility, suitable viscosity and injectability, appropriate mechanical properties and degradability, and excellent tissue repair performance. It can be used for various soft tissue repairs, including endometrial repair, vaginal repair, peritoneal lining repair, cartilage repair, superficial skin wound repair, skin scar removal, digestive tract repair, gastric wall repair, and urethral repair.

[0045] 2. Compared with stem cell repair, the intelligent dynamic directional assembly-disassembly soft tissue repair material prepared by this invention uses non-biotoxic components, is highly safe, has no ethical issues, is low in cost, is easy to operate, and has high versatility.

[0046] 3. When the target material is a solid, multiple negative pressure directional adsorption processes are used to form an oriented, highly oxidized structure. The layered, oriented carbonyl groups guide atoms with lone electrons to directionally attack positively charged carbon atoms, resulting in oriented covalent bonds ranging from low to high density. The degree of orientation can be controlled by adjusting the negative pressure adsorption pressure, the concentration of amine compounds, the number of adsorption cycles, and the pH value. This leads to a more stable multi-layered network, enabling the assembly of oriented composite materials with gradient bond concentrations.

[0047] 4. Compared to the processing method of this patent, ordinary processing results in insufficient conditions for subsequent reactions, difficulty in electron transfer, and unstable and difficult-to-occur reactions. When processing the target material, if the number of negative pressure adsorption cycles is less than 2, the chemical bonds formed by the reaction are unstable; if the number of cycles is greater than 5, it easily causes deformation of the target material and significant changes in its structure. During assembly, if the number of negative pressure adsorption cycles is less than 3, the chemical bonds formed by the reaction are unstable, and the amount assembled is small; if the number of cycles is greater than 4, the excessive amount of assembly makes it easy for collagen molecular chains to detach, and it easily causes deformation of the target material and significant changes in its structure.

[0048] 5. Compared with the processing method of this patent, when the semipermeable membrane is replaced less than 3 times, it will cause the target material or the loaded material to be non-uniform and there will be small molecule residues; when the pore size of the semipermeable membrane is too large, the reaction will be too rapid, causing polysaccharide non-uniformity and polysaccharide easy loss; when the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and there will be too many molecular residues.

[0049] 6. When the target material is a solid, it is assembled into an oriented composite material with a gradient concentration of chemical bonds. This oriented structure can achieve dynamic directional assembly-disassembly when the pH value changes, allowing amine compounds to be released directionally. In practical applications, amine compounds can be directionally released to the damaged site, and when the pH value rises, the amine compounds reassemble back into the composite material, making the material more suitable for long-term use and long-lasting soft tissue repair.

[0050] 7. When the target material is a liquid material, the multi-level semi-permeable membrane with small pores and large pores serves as a staged reaction site, which makes the diffusion and in-situ reaction slow and uniform, forming a highly uniform high oxidation state structure. The uniformly distributed carbonyl groups guide atoms with lone electrons to attack positively charged carbon atoms, so that the material forms relatively uniform chemical covalent bonds.

[0051] 8. The hierarchical semi-permeable membrane with micropores and macropores, acting as a staged reaction site, allows for slow and uniform diffusion and in-situ reactions. This enables amines and polysaccharides to undergo Michael addition reactions through the membrane, acquiring long-wavelength responsive characteristics. The distribution of relevant functional groups is also highly uniform. Under weakly acidic conditions, the high-oxidation-state target material and the long-wavelength responsive amines dissolve and mix uniformly. At this point, chemical covalent bonds do not react, and the amines and high-oxidation-state target material are evenly distributed through free diffusion and entanglement, resulting in a more compact molecular chain structure, which facilitates the next reaction. When the environment is changed to weakly alkaline, the two assemble to form highly uniform chemical bonds. The material viscosity increases, but it remains liquid and injectable. Under long-wavelength stimulation, the amines react and undergo secondary cross-linking, at which point the composite material transforms into a solid. This double cross-linking makes the material structure more stable and its mechanical strength higher.

[0052] 9. When the target material is in a liquid state, after the composite material is assembled and the environment is weakly acidic, the primary chemical bonds break. The material phase remains unchanged, but the structure and mechanical properties change. At any point in time, under long-wavelength directional stimulation such as infrared light, the molecular chains undergo violent vibrations, and amine compounds undergo directional assembly and disassembly. In the application scenario, amine compounds directionally enter the damaged tissue and exert their repair function.

[0053] 10. When the target material is in a liquid state, the prepared mixed solution is injectable and has high viscosity. It can be directly implanted into the damaged soft tissue via injection, making the operation simple. This allows the composite material to permeate the damaged area, increasing the contact area and probability between active groups and active factors and the tissue. The material can also be used when there is a need for filling the repaired area. Furthermore, it can achieve non-invasive shaping in vitro through long-wave stimulation.

[0054] 11. Characteristics of the final material: It is oriented, can release in a specific direction, can self-heal, is pH responsive, has increased mechanical properties, and its mechanical properties change with pH. Attached Figure Description

[0055] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0056] Figure 1 This is a schematic diagram of the negative pressure adsorption process when preparing repair materials using solid polymer materials.

[0057] Figure 2 This is a schematic diagram of the three-stage semi-permeable membrane reaction environment when preparing repair materials using liquid polymer materials. Detailed Implementation

[0058] To make the inventive objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be described in detail below with reference to specific embodiments. It should be understood that the embodiments described in this specification are merely illustrative and not intended to limit the invention. These embodiments are only for illustrating the invention and not for limiting its scope. Furthermore, various equivalent modifications made to the invention by those skilled in the art after reading the teachings of this invention also fall within the scope claimed by the claims of this application.

[0059] Example 1

[0060] Step 1: Use filter paper to absorb the surface moisture of the bacterial cellulose block, and then use negative pressure adsorption without filter paper to directly use the material as a reaction channel. Step 2: Perform the first negative pressure adsorption using a neutral-weakly alkaline buffer solution (Tris(hydroxymethyl)aminomethane) to provide a favorable microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the subsequent reaction conditions will be insufficient, electron transfer will be difficult, and the reaction will be unstable and unsustainable.

[0061] Step 3: A second negative pressure adsorption is performed using a 10% solution of a strong electron-gaining reagent (ferric chloride solution). Due to the pressure, most of the solute concentrates in the lower layer, creating a low-to-high concentration gradient within the gelatin block. Ions move from top to bottom, thus simultaneously creating a low-to-high stepwise reaction. The negative pressure adsorption pressure is 0.5 MPa, and the time is 100 s.

[0062] Step 4: Perform three negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (Tris(hydroxymethyl)aminomethane) to promote the forward reaction, stabilize the chemical bonds formed, foster the formation of a "low-high" chemical bond gradient within the target material, and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed are unstable; if the cycles are more than five, the target material is prone to deformation, resulting in significant changes to its structure.

[0063] Step 5: Use a 10% amine compound (human-like collagen solution) for negative pressure adsorption again. Similarly, a "low-high" solution concentration gradient is formed inside the bacterial cellulose, and ions move from top to bottom, thus simultaneously forming a "low-high" stepwise reaction degree and creating "few-many" chemical bonds. Repeat 3 times. When the negative pressure adsorption is repeated less than 3 times, the chemical bonds formed by the reaction are unstable and the amount of assembly is small; when the number of times is repeated more than 4 times, the amount of assembly is too large, the collagen molecular chains are easy to fall off, and it is easy to cause deformation of the target material, resulting in a significant change in the material structure.

[0064] Step Six: Perform negative pressure adsorption 2-5 times using a neutral-weakly alkaline buffer solution (Tris(hydroxymethyl)aminomethane) to stabilize the chemical bonds formed in the reaction and restore a favorable reaction microenvironment. If the number of negative pressure adsorption cycles is less than 2, the chemical bonds formed in the reaction are unstable; if the number of cycles is greater than 5, it can easily cause deformation of the target material and significant changes in its structure.

[0065] Example 2

[0066] Step 1: Prepare a 5% gelatin solution, dialyze for 3 days, and then freeze-dry to remove industrial impurities and improve the biocompatibility and purity of the material. Prepare a 3% homogeneous solution of the treated gelatin and place it in a 1000 kPa semi-permeable membrane as the primary reaction environment. Add a 15% methacrylic anhydride (MA) solution to a large beaker, seal the semi-permeable membrane containing gelatin, and place it in the MA solution, ensuring the solution completely submerges the membrane. Adjust the reaction temperature to 20℃. MA molecules will slowly pass through the semi-permeable membrane into the primary reaction environment and react with the gelatin molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing uneven reaction and clumping. Harmful molecules in the MA solution will be kept outside the semi-permeable membrane.

[0067] Step 2: After reacting for 6 hours, the semipermeable membrane is replaced with a 3000 kPa membrane as the secondary reaction environment, and the MA solution concentration is changed to 5%. The reaction continues at 20°C. After the primary reaction, most of the functional groups are reacted, which makes the reaction more complete and ensures that the reaction of all molecular chains occurs simultaneously.

[0068] Step 3: After 6 hours of reaction, the semipermeable membrane was replaced with a 10000 kPa membrane to create a tertiary reaction environment. The MA solution was replaced with PBS solution, and the PBS solution was changed every 6 hours. The reaction was carried out at 30°C for 48 hours. Under the tertiary reaction environment, all reactions gradually ceased, and residual small molecules diffused out of the semipermeable membrane. This ensured the homogeneity and biocompatibility of the modified polysaccharide.

[0069] When the semipermeable membrane is replaced less than 3 times, the polysaccharides will become uneven and small molecules will remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven polysaccharides and easy loss of polysaccharides. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0070] Step 4: After purifying the dextran using the method described in Step 1, prepare a 5% solution using a neutral-weakly alkaline buffer (Tris(hydroxymethyl)aminomethane) solution. Place this solution in a 500 kPa semipermeable membrane as the primary reaction environment. Prepare a 5% solution of a strong electron-gathering reagent (ferric chloride). Seal the semipermeable membrane containing the dextran and place it in the strong electron-gathering solution, ensuring the solution completely submerges the membrane. Adjust the reaction temperature to 20°C. The strong electron-gathering molecules slowly pass through the semipermeable membrane into the primary reaction environment and react with the dextran molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing inconsistent oxidation state progression.

[0071] Step 5: After reacting for 1 hour, replace the semipermeable membrane with a 1000 kPa membrane as the secondary reaction environment, change the concentration of the strong electron-accepting reagent to 1%, and continue the reaction at 20°C. After the primary reaction, most of the functional groups are reacted, which can make the reaction more complete, ensure that the reaction of all molecular chains occurs simultaneously, and at the same time, make the reaction rate stable and ensure the uniformity of the product.

[0072] Step Six: After 1 hour of reaction, replace the semipermeable membrane with a 5000 kPa membrane to create a tertiary reaction environment. Replace the strong electron-accepting reagent with PBS solution, changing the PBS solution every 6 hours. Incubate at 30°C for 48 hours. In the tertiary reaction environment, all reactions gradually cease, and residual small molecules diffuse out of the semipermeable membrane. This ensures the homogeneity and biocompatibility of the target material after oxidation state upgrade.

[0073] When the semipermeable membrane is replaced less than 3 times, it will cause uneven loading and small molecules to remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven loading and large molecules will easily be lost. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0074] Step 7: After freeze-drying the upgraded oxidized dextran and modified gelatin separately, prepare a 5% solution with a slightly acidic buffer, mix them thoroughly, and then add a slightly alkaline buffer to react for 1-5 hours, so that the pH of the solution is between 7.5 and 8.5. This yields mixed solution C.

[0075] Step 8: Inject the mixed solution C into a container of any shape and space, and use long waves to initiate self-polymerization, causing the amine compounds to undergo a secondary cross-linking reaction, and the material is transformed into a solid.

[0076] Example 3

[0077] Step 1: Use filter paper to absorb the surface moisture of the polyurethane, and then use negative pressure adsorption without filter paper to directly use the material as a reaction channel. Step 2: Perform the first negative pressure adsorption using a neutral-weakly alkaline buffer solution (triethanolamine solution) to provide a favorable reaction microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the subsequent reaction conditions will be insufficient, electron transfer will be difficult, and the reaction will be unstable and unsustainable.

[0078] Step 3: A second negative pressure adsorption is performed using a 15% strong electron-gaining reagent solution (sodium periodate solution). Due to the pressure, most of the solute concentrates in the lower layer, creating a low-to-high concentration gradient within the gelatin block. Ions move from top to bottom, thus simultaneously creating a low-to-high stepwise reaction. The negative pressure adsorption pressure is 0.2 MPa, and the time is 600 s.

[0079] Step 4: Perform four negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (triethanolamine solution) to promote the forward reaction, stabilize the chemical bonds formed, foster the formation of a "low-high" chemical bond gradient within the target material, and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed are unstable; if the cycles are more than five, the target material is prone to deformation, resulting in significant changes to its structure.

[0080] Step 5: Use a 15% amine compound (human-like collagen solution) for another negative pressure adsorption. Similarly, a low-to-high concentration gradient forms within the bacterial cellulose, causing ions to move from top to bottom, thus simultaneously forming a low-to-high stepwise reaction and creating fewer-to-more chemical bonds. Repeat this process four times. If the negative pressure adsorption is repeated less than three times, the chemical bonds formed are unstable, and the amount of assembly is small. If the number of repetitions is greater than four times, the collagen molecular chains are easily detached, which can easily cause deformation of the target material and significant changes in its structure.

[0081] Step Six: Perform four negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (triethanolamine solution) to stabilize the chemical bonds formed in the reaction and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed in the reaction are unstable; if the cycles are more than five, it can easily cause deformation of the target material and significant changes in its structure.

[0082] Example 4

[0083] Step 1: Prepare a 10% chitosan solution, dialyze for 5 days, and then freeze-dry to remove industrial impurities and improve the biocompatibility and purity of the material. Prepare a 10% homogeneous chitosan solution and place it in a 2000 kPa semi-permeable membrane as the primary reaction environment. Add a 20% methacrylic anhydride (MA) solution to a large beaker, seal the semi-permeable membrane containing chitosan, and place it in the MA solution, ensuring the solution completely submerges the membrane. Adjust the reaction temperature to 40℃. MA molecules will slowly enter the primary reaction environment through the semi-permeable membrane and react with the chitosan molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing uneven reaction and clumping. Harmful molecules in the MA solution are kept outside the semi-permeable membrane.

[0084] Step 2: After reacting for 12 hours, the semipermeable membrane is replaced with one at 7000 kPa as the secondary reaction environment, and the concentration of the MA solution is changed to 15%. The reaction continues at 40°C. After the primary reaction, most of the functional groups are reacted, which makes the reaction more complete and ensures that the reaction of all molecular chains occurs simultaneously.

[0085] Step 3: After 12 hours of reaction, the semipermeable membrane was replaced with one at 15000 kPa to create a tertiary reaction environment. The MA solution was replaced with PBS solution, and the PBS solution was changed every 12 hours. The reaction was carried out at 40°C for 96 hours. Under the tertiary reaction environment, all reactions gradually ceased, and residual small molecules diffused out of the semipermeable membrane. This ensured the homogeneity and biocompatibility of the modified polysaccharide.

[0086] When the semipermeable membrane is replaced less than 3 times, the chitosan will become uneven and small molecules will remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven products and easy loss. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0087] Step 4: After purifying the collagen using the method described in Step 1, prepare a 10% solution using a neutral-weakly alkaline buffer (triethanolamine solution). Place this solution in a 1000 kPa semipermeable membrane as the primary reaction environment. Prepare a 10% solution of a strong electron-accepting reagent (sodium periodate). Seal the semipermeable membrane containing the collagen and place it in the solution of the strong electron-accepting reagent, ensuring the solution completely submerges the membrane. Adjust the reaction temperature to 30℃. Strong electron-accepting molecules slowly pass through the semipermeable membrane into the primary reaction environment and react with the collagen molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing inconsistent oxidation state progression.

[0088] Step 5: After reacting for 2 hours, replace the semipermeable membrane with a 5000 kPa membrane as the secondary reaction environment, change the concentration of the strong electron-accepting reagent to 5%, and continue the reaction at 30°C. After the primary reaction, most of the functional groups are reacted, which can make the reaction more complete, ensure that the reaction of all molecular chains occurs simultaneously, and at the same time, make the reaction rate stable and ensure the uniformity of the product.

[0089] Step Six: After 2 hours of reaction, replace the semipermeable membrane with a 10000 kPa system to create a tertiary reaction environment. Replace the strong electron-accepting reagent with PBS solution, changing the PBS solution every 12 hours. Incubate at 40°C for 48 hours. In this tertiary reaction environment, all reactions gradually cease, and residual small molecules diffuse out of the semipermeable membrane. This ensures the homogeneity and biocompatibility of the target material after oxidation state upgrade.

[0090] When the semipermeable membrane is replaced less than 3 times, it will cause uneven loading and small molecules to remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven loading and large molecules will easily be lost. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0091] Step 7: After freeze-drying the oxidized collagen and modified chitosan separately, prepare a 20% solution with a slightly acidic buffer, mix them thoroughly, and then add a slightly alkaline buffer to react for 1-5 hours, so that the pH of the solution is between 7.5 and 8.5. This yields mixed solution C.

[0092] Step 8: Inject the mixed solution C into a container of any shape and space, and use long waves to initiate self-polymerization, causing the amine compounds to undergo a secondary cross-linking reaction, and the material is transformed into a solid.

[0093] Example 5

[0094] Step 1: Use filter paper to absorb the surface moisture of PLA, and then use negative pressure adsorption without filter paper to directly use the material as a reaction channel. Step 2: Perform the first negative pressure adsorption using a neutral-weakly alkaline buffer solution (glycine-sodium hydroxide solution) to provide a favorable reaction microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the subsequent reaction conditions will be insufficient, electron transfer will be difficult, and the reaction will be unstable and unsustainable.

[0095] Step 3: A second negative pressure adsorption is performed using a 15% strong electron-gaining reagent solution (potassium permanganate solution). Due to the pressure, most of the solute concentrates in the lower layer, creating a low-to-high concentration gradient within the PLA. Ions move from top to bottom, thus simultaneously creating a low-to-high stepwise reaction. The negative pressure adsorption pressure is 1 MPa, and the time is 300 s.

[0096] Step 4: Perform four negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (glycine-sodium hydroxide solution) to promote the forward reaction, stabilize the chemical bonds formed, and foster the formation of a "low-high" chemical bond gradient within the target material, while simultaneously restoring a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed are unstable; if the cycles are more than five, the target material is prone to deformation, resulting in significant changes to its structure.

[0097] Step 5: Use a 12% amine compound (peptide solution) for another negative pressure adsorption. Similarly, a low-to-high concentration gradient is formed within the PLA, causing ions to move from top to bottom, thus simultaneously forming a low-to-high stepwise reaction and creating fewer-to-more chemical bonds. Repeat this process three times. If the negative pressure adsorption is repeated less than three times, the chemical bonds formed are unstable, and the amount of assembly is small. If the number of repetitions is greater than four times, the amount of assembly is excessive, collagen molecular chains are easily detached, and the target material is easily deformed, resulting in a significant change in the material structure.

[0098] Step Six: Perform three negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (glycine-sodium hydroxide solution) to stabilize the chemical bonds formed in the reaction and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed in the reaction are unstable; if the cycles are more than five, it can easily cause deformation of the target material and significant changes in its structure.

[0099] Example 6

[0100] Step 1: Prepare 10% solutions of human-like collagen and hyaluronic acid separately. Dialyze each solution for 5 days, then freeze-dry to remove industrial impurities and improve biocompatibility and purity. Prepare a 10% homogeneous mixture of the treated human-like collagen and hyaluronic acid in a 1:1 neutral-weakly alkaline buffer solution (glycine-sodium hydroxide solution). Place this mixture in a 2000 kPa semipermeable membrane as the primary reaction environment. Add 20% methacrylic anhydride (MA) solution to a large beaker. Seal the semipermeable membrane containing the mixture and place it in the MA solution, ensuring the solution completely submerges the membrane. Set the reaction temperature to 30℃. MA molecules will slowly pass through the semipermeable membrane into the primary reaction environment and react with the molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing uneven reaction and clumping. Harmful molecules in the MA solution will be kept outside the semipermeable membrane.

[0101] Step 2: After reacting for 10 hours, the semipermeable membrane is replaced with a 5000 kPa membrane as the secondary reaction environment, and the concentration of the MA solution is changed to 10%. The reaction continues at 30°C. After the primary reaction, most of the functional groups are reacted, which makes the reaction more complete and ensures that the reaction of all molecular chains occurs simultaneously.

[0102] Step 3: After 10 hours of reaction, the semipermeable membrane was replaced with one at 12000 kPa to create a tertiary reaction environment. The MA solution was replaced with PBS solution, and the PBS solution was changed every 10 hours. The reaction was carried out at 30°C for 48 hours. In the tertiary reaction environment, all reactions gradually ceased, and residual small molecules diffused out of the semipermeable membrane. This ensured the homogeneity and biocompatibility of the modified mixture.

[0103] When the semipermeable membrane is replaced less than 3 times, the mixed material will be uneven and small molecules will remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven mixing and easy loss. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0104] Step 4: Prepare a 10% solution of sulfanilamide chitosan using a neutral-weakly alkaline buffer solution. Place this solution in an 800 kPa semi-permeable membrane as the primary reaction environment. Prepare a 10% solution of a strong electron-gathering reagent (potassium permanganate), seal it with the semi-permeable membrane, and place it in the solution of the strong electron-gathering reagent, ensuring the solution completely submerges the semi-permeable membrane. Adjust the reaction temperature to 30℃. The strong electron-gathering molecules slowly enter the primary reaction environment through the semi-permeable membrane and react with the molecular chains. This allows for controlled reaction rate, resulting in a more uniform and complete reaction, preventing inconsistent oxidation state progression.

[0105] Step 5: After reacting for 2 hours, replace the semipermeable membrane with a 4000 kPa membrane as the secondary reaction environment. Change the concentration of the strong electron-accepting reagent to 3% and continue the reaction at 30°C. After the first-stage reaction, most of the functional groups are reacted, which makes the reaction more complete, ensures that the reaction of all molecular chains occurs simultaneously, and also makes the reaction rate stable, ensuring the uniformity of the product.

[0106] Step Six: After 2 hours of reaction, replace the semipermeable membrane with one at 8000 kPa to create a tertiary reaction environment. Replace the strong electron-accepting reagent with PBS solution, changing the PBS solution every 10 hours. Incubate at 30°C for 72 hours. In this tertiary reaction environment, all reactions gradually cease, and residual small molecules diffuse out of the semipermeable membrane. This ensures the homogeneity and biocompatibility of the target material after oxidation state upgrade.

[0107] When the semipermeable membrane is replaced less than 3 times, it will cause uneven loading and small molecules to remain. When the pore size of the semipermeable membrane is too large, the reaction will be too rapid, resulting in uneven loading and large molecules will easily be lost. When the pore size of the semipermeable membrane is too small, molecules will have difficulty passing through, the reaction will be too slow or even not occur, and too many molecules will remain.

[0108] Step 7: After freeze-drying the modified human-like collagen and hyaluronic acid mixture and the oxidized chitosan, prepare a 10% solution with a slightly acidic buffer, mix them thoroughly, and then add a slightly alkaline buffer to react for 1-5 hours, so that the pH of the solution is between 7.5 and 8.5. This yields mixed solution C.

[0109] Step 8: Inject the mixed solution C into a container of any shape and space, and use long waves to initiate self-polymerization, causing the amine compounds to undergo a secondary cross-linking reaction, and the material is transformed into a solid.

[0110] Example 7

[0111] Step 1: After the cellulose is crushed, it is separated into a suspension using a cell disruptor. After heating and mixing with gelatin, a solid membrane material is formed. The surface moisture is absorbed with filter paper, and negative pressure adsorption is performed without filter paper, so that the material can be directly used as a reaction channel. Step 2: Perform the first negative pressure adsorption using a neutral-weakly alkaline buffer solution (sodium carbonate-sodium hydroxide solution) to provide a favorable microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the conditions for subsequent reactions will be insufficient, electron transfer will be difficult, and the reaction will be unstable and unsustainable.

[0112] Step 3: A second negative pressure adsorption is performed using a 5% strong electron-gaining reagent solution (sodium hypochlorite solution). Due to the pressure, most of the solute concentrates in the lower layer, creating a low-to-high concentration gradient within the material block. Ions move from top to bottom, thus simultaneously creating a low-to-high stepwise reaction. The negative pressure adsorption pressure is 2 MPa, and the time is 600 s.

[0113] Step 4: Perform two negative pressure adsorption cycles using a weakly alkaline buffer solution (sodium carbonate-sodium hydroxide solution) to promote the forward reaction, stabilize the chemical bonds formed, and foster the formation of a "low-high" chemical bond gradient within the target material, while simultaneously restoring a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed are unstable; if the cycles are more than five, the target material is prone to deformation, resulting in significant changes to its structure.

[0114] Step 5: Use a 15% amine compound (fish collagen solution) for negative pressure adsorption again. Similarly, a "low-high" solution concentration gradient is formed inside the composite membrane, and ions move from top to bottom, thus simultaneously forming a "low-high" stepwise reaction degree and creating "few-many" chemical bonds. Repeat 3 times. When the negative pressure adsorption is repeated less than 3 times, the chemical bonds formed by the reaction are unstable and the assembly amount is small; when the number of times is more than 4, the assembly amount is too large, the collagen molecular chains are easy to fall off, and it is easy to cause deformation of the target material, resulting in a significant change in the material structure.

[0115] Step Six: Perform three negative pressure adsorption cycles using a weakly alkaline buffer solution (sodium carbonate-sodium hydroxide solution) to stabilize the chemical bonds formed in the reaction and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed in the reaction are unstable; if the cycles are more than five, it can easily cause deformation of the target material and significant changes in its structure.

[0116] Example 8

[0117] Step 1: After the cellulose is broken down, it is separated into a suspension using a cell disruptor. It is then blended with polyurethane to form a solid membrane material. The surface moisture is absorbed with filter paper, and negative pressure adsorption is performed without filter paper, thus directly using the material as a reaction channel. Step 2: Perform the first negative pressure adsorption using a neutral-weakly alkaline buffer solution (sodium carbonate-sodium hydroxide solution) to provide a favorable microenvironment for subsequent reactions, facilitating electron transfer. Without this step, the conditions for subsequent reactions will be insufficient, electron transfer will be difficult, and the reaction will be unstable and unsustainable.

[0118] Step 3: A second negative pressure adsorption is performed using a 15% solution of a strong electron-gaining reagent (ferric chloride solution). Due to the pressure, most of the solute concentrates in the lower layer, creating a low-to-high concentration gradient within the material block. Ions move from top to bottom, thus simultaneously creating a low-to-high stepwise reaction. The negative pressure adsorption pressure is 0.2 MPa, and the time is 600 s.

[0119] Step 4: Perform three negative pressure adsorption cycles using a neutral-weakly alkaline buffer solution (sodium carbonate-sodium hydroxide solution) to promote the forward reaction, stabilize the chemical bonds formed, foster the formation of a "low-high" chemical bond gradient within the target material, and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are fewer than two, the chemical bonds formed are unstable; if the cycles are more than five, the target material is prone to deformation, resulting in significant changes to its structure.

[0120] Step 5: Use a 15% peptide solution for negative pressure adsorption again. Similarly, a low-to-high concentration gradient is formed inside the composite membrane, causing ions to move from top to bottom, thus simultaneously forming a low-to-high stepwise reaction and creating fewer-to-more chemical bonds. Repeat this process three times. If the negative pressure adsorption is repeated less than three times, the chemical bonds formed are unstable, and the amount of assembly is small. If the number of repetitions is greater than four times, the amount of assembly is excessive, collagen molecular chains are easily detached, and the target material is easily deformed, resulting in a significant change in the material structure.

[0121] Step Six: Perform three negative pressure adsorption cycles using a weakly alkaline buffer solution (neutral-weakly alkaline buffer solution, sodium carbonate-sodium hydroxide solution) to stabilize the chemical bonds formed in the reaction and restore a favorable reaction microenvironment. If the negative pressure adsorption cycles are less than two, the chemical bonds formed in the reaction are unstable; if the cycles are more than five, it can easily cause deformation of the target material and significant changes in its structure.

[0122] Example 9

[0123] When the material in Example 1 is applied to damaged tissues such as abdominal wall wounds, the oriented composite material structure with gradient chemical bond concentrations can achieve dynamic directional assembly-disassembly when the pH value changes, since the pH value of the wound microenvironment is different from that of healthy tissue. This allows collagen to be released directionally to the damaged site. When the pH value rises, amine compounds are reassembled back into the composite material, making the material more suitable for long-term use, promoting wound healing while inhibiting excessive proliferation.

[0124] Example 10

[0125] When the material from Example 2 is injected into damaged tissue, such as a damaged urethra, and the composite material is assembled and molded, the primary chemical bonds break in a weakly acidic environment. The material phase remains unchanged, but its structure and mechanical properties alter, and the composite material infiltrates the damaged area. At any point in time, under long-wavelength directional stimulation such as infrared radiation, the molecular chains undergo violent vibrations, and amine compounds undergo directional assembly and disassembly to perform repair functions while preventing problems such as fibrosis caused by over-repair.

[0126] When the target material is in a liquid state, the prepared mixed solution is injectable and has a high viscosity. It can be directly implanted into the damaged soft tissue by injection, which is simple to operate and allows the composite material to wet the damaged area, increasing the contact area and contact probability between the active groups and active factors and the tissue.

[0127] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this invention, and these modifications or substitutions should all be covered within the scope of protection of this invention. Therefore, the scope of protection of this invention should be determined by the scope defined in the claims.

Claims

1. A smart dynamic directional assembly-disassembly soft tissue repair material, characterized in that: The soft tissue repair material is made from biopolymers and amine compounds through a nucleophilic addition reaction; The nucleophilic addition reaction is as follows: the atom with lone pair electrons in the amine compound attacks the carbon atom with positive charge on the carbonyl group in the biopolymer to form an α-hydroxy compound, which is then dehydrated to form a covalent bond, thus obtaining the amine compound molecular chain; The aforementioned biopolymer materials are treated with reagents that have strong electron-gaining ability to upgrade their oxidation state; The aforementioned biopolymer materials are either solid biopolymer materials or liquid biopolymer materials; If the biopolymer material is a liquid biopolymer material, the amine compound that undergoes affinity addition with it should first be modified by reacting with a Michael addition reagent; The aforementioned amine compounds repair soft tissue damage through directional assembly-disassembly of their molecular chains.

2. The intelligent dynamic directional assembly-disassembly soft tissue repair material according to claim 1, characterized in that: The solid biopolymer material is specifically one or a combination of two or more of the following: lignin, cellulose, bacterial cellulose, cellulose nanomaterials, gelatin, polyurethane, or PLA. The liquid biopolymer material specifically comprises one or more of the following: dextran, chitosan, chitosan derivatives, alginate, modified alginate, polypeptide, protein, or collagen. The amine compounds are selected from polysaccharides, proteins, collagen, polypeptides, growth factors, or nucleic acids.

3. The preparation method of the intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 2, characterized in that, Includes the following steps: Step 1: The solid biopolymer material is subjected to a first negative pressure adsorption using a neutral-weakly alkaline buffer solution; Step 2: A second negative pressure adsorption is performed using a reagent solution with strong electron-gaining ability; Step 3: Perform negative pressure adsorption 2-4 times using a neutral-weakly alkaline buffer solution; Step 4: Perform negative pressure adsorption 2-4 times using an amine compound solution; Step 5: Perform negative pressure adsorption 2-5 times using a neutral-weakly alkaline buffer solution to obtain intelligent dynamic directional assembly-disassembly soft tissue repair material.

4. The preparation method of an intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 2, characterized in that: The neutral-weakly alkaline buffer solution mentioned in steps 1, 3 and 5 is selected from tris(hydroxymethyl)aminomethane (Tris) solution, triethanolamine solution, glycine-sodium hydroxide solution or sodium carbonate-sodium hydroxide solution; The concentration of the neutral-weakly alkaline buffer solution is 5 wt%-20 wt%. The strong electron-donating reagent mentioned in step 2 is selected from ferric chloride, sodium periodate, potassium permanganate, and sodium hypochlorite, and the concentration of the strong electron-donating reagent solution is 1 wt%-10 wt%. The negative pressure adsorption conditions described in steps 1-5 are: negative pressure adsorption pressure 0.2MPa-2MPa, time 30s-600s.

5. The preparation method of an intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 2, characterized in that, Includes the following steps: Step 1: Dissolve the amine compound in buffer solution to prepare a solution, place the solution in a semi-permeable membrane, and seal it to obtain a primary reaction environment; Step 2: Place the first-order reaction environment obtained in Step 1 into a Michael addition reagent solution to carry out the reaction; Step 3: Place the liquid in the primary reaction environment obtained in Step 2 into a semi-permeable membrane and seal it to obtain the secondary reaction environment; Step 4: Place the secondary reaction environment obtained in Step 3 into a Michael addition reagent solution to carry out the reaction; Step 5: Place the liquid in the secondary reaction environment described in Step 4 into a semi-permeable membrane and seal it to obtain the tertiary reaction environment. Step 6: Place the tertiary reaction environment obtained in Step 5 into PBS solution to carry out the reaction and obtain the modified amine compound; Step 7: Dissolve the liquid biopolymer material in a neutral-weakly alkaline buffer solution to prepare a solution, and place the solution in a semipermeable membrane as the primary reaction environment; Step 8: Place the first-order reaction environment obtained in step 7 into a solution of a strong electron-gaining reagent to carry out the reaction; Step 9: Place the liquid in the primary reaction environment described in Step 8 into a semi-permeable membrane and seal it to obtain the secondary reaction environment. Step 10: Place the secondary reaction environment obtained in step 9 into a solution of a strong electron-gaining reagent to carry out the reaction; Step 11: Place the liquid in the secondary reaction environment described in step 10 into a semi-permeable membrane and seal it to obtain the tertiary reaction environment; Step 12: Place the tertiary reaction environment obtained in step 11 into a PBS solution to carry out the reaction and obtain an oxidized liquid biopolymer material. Step 13: The modified amine compound obtained in step 6 and the oxidized upgraded liquid biopolymer obtained in step 12 are respectively prepared into solutions with acidic buffer solution, mixed evenly, and then reacted with alkaline buffer solution to obtain intelligent dynamic directional assembly-disassembly soft tissue repair material.

6. The preparation method of the intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 5, characterized in that: The concentration of the solution mentioned in step 1 is 3 wt%-10 wt%, and the semipermeable membrane is a semipermeable membrane with a pressure of 1000 kPa-2000 kPa; The Michael addition reagent mentioned in step 2 is methacrylic anhydride or methacrylamide, the concentration of the strong electron-gathering reagent solution is 15 wt%-20 wt%, the reaction temperature is 20℃-40℃, and the reaction time is 6-12h; The semipermeable membrane mentioned in step 3 is a semipermeable membrane with a pressure of 3000 kPa to 7000 kPa; The Michael addition reagent mentioned in step 4 is methacrylic anhydride or methacrylamide, the concentration of the strong electron-gathering reagent solution is 5 wt%-15 wt%, the reaction temperature is 20℃-40℃, and the reaction time is 6-12h; The semipermeable membrane mentioned in step 5 is a semipermeable membrane with a pressure of 10000 kPa to 15000 kPa; The reaction conditions described in step 6 are as follows: the PBS solution is replaced every 6-12 hours, the reaction temperature is 30℃-40℃, the total reaction time is 48-96 hours, and the total number of replacements is greater than 3. The neutral-weakly alkaline buffer solution mentioned in step 7 has a concentration of 5 wt%-10 wt%; the semipermeable membrane is a semipermeable membrane with a pressure of 500 kPa-1000 kPa. The strong electron-gaining reagent mentioned in step 8 is ferric chloride, sodium periodate, potassium permanganate and sodium hypochlorite. The concentration of the strong electron-gaining reagent solution is 5 wt%-10 wt%, the reaction temperature is 20℃-30℃, and the reaction time is 1-2h. The semipermeable membrane mentioned in step 9 is a semipermeable membrane with a pressure of 1000 kPa to 5000 kPa; The strong electron-gaining reagent mentioned in step 10 is ferric chloride, sodium periodate, potassium permanganate and sodium hypochlorite. The concentration of the strong electron-gaining reagent solution is 1 wt%-5 wt%, the reaction temperature is 20℃-30℃, and the reaction time is 1-2h. The semipermeable membrane mentioned in step 11 is a semipermeable membrane with a pressure of 5000 kPa to 10000 kPa; The reaction conditions described in step 12 are as follows: the PBS solution is replaced every 6-12 hours, the reaction temperature is 30℃-40℃, the total reaction time is 48-96 hours, and the total number of replacements is greater than 3. The slightly acidic buffer solution mentioned in step 13 is 50 mM Glycine-HCl, 50 mM acetate buffer, or 50 mM citrate buffer; the slightly alkaline buffer solution is 50 mM carbonate buffer; the concentration of the solution prepared by the slightly acidic buffer solution is 5 wt%-20 wt%, and the reaction time is 1-5 h.

7. The intelligent dynamic directional assembly-disassembly soft tissue repair material prepared by the method according to any one of claims 3 to 6.

8. The application of the intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 7, characterized in that: The aforementioned soft tissue repair material repairs soft tissue damage by implanting it into or covering the damaged soft tissue area.

9. The application of the intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 7, characterized in that: The aforementioned soft tissue repair material is injected into the damaged soft tissue area to repair soft tissue damage.

10. The application of the intelligent dynamic directional assembly-disassembly soft tissue repair material as described in claim 8 or 9, characterized in that: The aforementioned soft tissue repair material is applied to the repair of the epidermis.